Phase I Trial of Intratumoral Injection of CCL21 Gene–Modified Dendritic Cells in Lung Cancer Elicits Tumor-Specific Immune Responses and CD8+ T-cell Infiltration - Lee, Jay M.; Lee, Mi-Heon; Garon, Edward; Goldman, Jonathan W.; Salehi-Rad, Ramin; Baratelli, Felicita E.; Schaue, Dörthe; Wang, Gerald; Rosen, Fran; Yanagawa, Jane; Walser, Tonya C.; Lin, Ying; et al. (Clinical cancer research, 2017)
Purpose: A phase I study was conducted to determine safety, clinical efficacy, and antitumor immune responses in patients with advanced non–small cell lung carcinoma (NSCLC) following intratumoral administration of autologous dendritic cells (DC) transduced with an adenoviral (Ad) vector expressing the CCL21 gene (Ad-CCL21-DC). We evaluated safety and tumor antigen–specific immune responses following in situ vaccination (ClinicalTrials.gov: NCT01574222). Experimental Design: Sixteen stage IIIB/IV NSCLC subjects received two vaccinations (1 × 106, 5 × 106, 1 × 107, or 3 × 107 DCs/injection) by CT- or bronchoscopic-guided intratumoral injections (days 0 and 7). Immune responses were assessed by tumor antigen–specific peripheral blood lymphocyte induction of IFNγ in ELISPOT assays. Tumor biopsies were evaluated for CD8+ T cells by IHC and for PD-L1 expression by IHC and real-time PCR (RT-PCR). Results: Twenty-five percent (4/16) of patients had stable disease at day 56. Median survival was 3.9 months. ELISPOT assays revealed 6 of 16 patients had systemic responses against tumor-associated antigens (TAA). Tumor CD8+ T-cell infiltration was induced in 54% of subjects (7/13; 3.4-fold average increase in the number of CD8+ T cells per mm2). Patients with increased CD8+ T cells following vaccination showed significantly increased PD-L1 mRNA expression. Conclusions: Intratumoral vaccination with Ad-CCL21-DC resulted in (i) induction of systemic tumor antigen–specific immune responses; (ii) enhanced tumor CD8+ T-cell infiltration; and (iii) increased tumor PD-L1 expression. Future studies will evaluate the role of combination therapies with PD-1/PD-L1 checkpoint inhibition combined with DC-CCL21 in situ vaccination. Clin Cancer Res; 23(16); 4556–68. ©2017 AACR.